Penerapan Metode Transformasi Brovey Pada Pembesaran Citra Ultrasonografi (USG) - Aslinawati Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
In the process of taking an ultrasound image or the results of long-distance imaging with a telescope or the results of medical recordings including x-rays, ultrasound or scans, there are often disturbances in the form of light distortion, noise or other disturbances that cause objects in the image to be unclear or blurry. Medical ultrasonography (sonography ) is an imaging diagnostic technique using ultra sound that is used to image internal organs and muscles, their size, structure, and wound pathology, making this technique useful for examining organs. Obstetric sonography is commonly used during pregnancy. Image processing applications are increasingly widespread as in the medical world, image processing has a very large role in everyday life. In the field of ultrasound medicine or better known by the abbreviation USG is widely used in medical. Enlargement or zooming is a process carried out to enlarge an image. The enlargement process certainly has blur in the image so that the image will look like boxes. And there is a change in the size of the image This happens because in the enlargement process, the resolution that compiles the image becomes smaller to reduce it. Image enlargement is one of the fields in digital image processing that is getting enough attention because of the large need to obtain a better view or view of an image as for the method used is the brovey transformation method. Brovey transformation method is an easy method for combining data from different sensors. In this thesis will be discussed on how to create an image enlargement application using the brovey transformation method. This application was built with Matlab 2013 as an editor for editing programs